Evaluation of All Surgical Margins in Pancreatic Resection Specimens by Proper Grossing Techniques: Surgical Pathology Experience of 285 Cases - Özgür EKİNCİ (Federation of Turkish Pathology Societies, 2018)
Objective: The aim of this study was to review our series of pancreatic resection specimen handling results and focus on the positivity of the tumor in various retroperitoneal surgical margins. Material and Method: Our archival cases from 2008 to 2018 were retrospectively examined, especially for the surgical margins. The demographics, tumor locations, and the diagnoses were recorded. The state of all of the retropancreatic surgical margins (anterior, posterior, superior, inferior, superior mesenteric vein and artery) were recorded. Results: There were 285 cases, of which 157 were male and 128 female. The mean and median ages were 63.3 and 64, respectively. Invasive ductal adenocarcinoma was the most common diagnosis [202 cases (70.8%)]. Positivity was observed in 90 (31.5%) margins. The majority was in the superior mesenteric vein margin [n:24 (8.4%)]. This was followed by the anterior, resection and SMA margins. Conclusion: Pancreatic resections should macroscopically be sampled by recommended methods in order to detect positivity in individual margins by proper grossing techniques. When this is applied, the superior mesenteric vein margin is the margin most prone to be positive for the tumor.